Impact of nurturing care educational videos focusing on children with nutritional problems aged 6-23 months on mothers' knowledge and child growth - Fitri Haryanti; Lely Lusmilasari; Sri Hartini; Ayyu Sandhi; Ika Parmawati; Akhmadi Akhmadi; Nisa Nur Hasanah; Fitriana Andarwati; Hani Risnawati; Alissa Nur Pratiwi; Ananda Sekar Kusumawati; Redyta Dwi Cahyani (Medisains)
Background: The first 1,000 days are crucial for a child's development. Indonesia has limited research on responsive caregiving and early learning opportunities, especially for children with nutritional challenges. While studies have addressed general child nutrition, few have explored comprehensive nurturing care interventions. This gap underscores the need for further research. Educational videos, particularly animated ones, effectively capture attention and improve understanding, making them valuable for enhancing maternal knowledge and child growth.